If fx = x - 3, then f'(3) is from Mathe

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

Advertisement

831.

If fx = x - 3, then f'(3) is

  • - 1

  • 1

  • 0

  • does not exist


D.

does not exist

Given, fx = x - 3Redefine this function;  fx = 3 - x, x < 30       , x = 3x - 3, x > 3f'x = - 1, x < 30    , x = 31    , x > 3It is clear that, Lf'(3) *Rf'(3). f'3 does not exist.

 


Advertisement
832.

If fx = xsin1x, x  00           , x = 0, then at x = 0 the function f(x) is

  • continuous

  • differentiable

  • continuous but not differentiable

  • None of the above


833.

If Rolle's theorem for f(x) = exsinx - cosx is verified on π4, 5π4, then the value of c is

  • π3

  • π2

  • 3π4

  • π


834.

If the function f(x) defined by

fx = xsin1x, for x  0k,            for x  = 0

is continuous at x = 0, then k is equal to

 

  • 0

  • 1

  • - 1

  • 12


Advertisement
835.

If y = emsin-1x and 1 - x2dydx2 = Ay2, then A is equal to

  • m

  • - m

  • m2

  • - m2


836.

For what value of k, the function defined by

f(x) = log1 + 2xsinx°x2, for x  0k                             , for x = 0

is continuous at x = 0 ?

  • 2

  • 12

  • π90

  • 90π


837.

If log10x2 - y2x2 + y2 = 2, then dydx is equal to

  • - 99x101y

  • 99x101y

  • - 99y101x

  • 99y101x


838.

If g(x) is the inverse function of f(x) and f'x = 11 +x4, then g'(x) is

  • 1 + [g(x)]4

  • 1 - [g(x)]4

  • 1 + [f(x)]4

  • 11 + g(x)4


Advertisement
839.

If the function f(x) = tanπ4 + x1x for x  0 is  = K for x = 0 continuous at x = 0, then K = ?

  • e

  • e- 1

  • e2

  • e- 2


840.

If x = f(t) and y = g(t) are differentiable functions of t, then d2ydx2 is

  • f't . g''t - g't . f''tf't3

  • f't . g''t - g't . f''tf't2

  • g't . f''t - f't . g''tf't3

  • g't . f''t + f't . g''tf't3


Advertisement